The Evolutionary Dance between Innate Host Antiviral Pathways and SARS-CoV-2 - Saba R. Aliyari; Natalie Quanquin; Olivier Pernet; Shilei Zhang; Lulan Wang; Genhong Cheng (Pathogens, 2022)
Compared to what we knew at the start of the SARS-CoV-2 global pandemic, our understanding of the interplay between the interferon signaling pathway and SARS-CoV-2 infection has dramatically increased. Innate antiviral strategies range from the direct inhibition of viral components to reprograming the host’s own metabolic pathways to block viral infection. SARS-CoV-2 has also evolved to exploit diverse tactics to overcome immune barriers and successfully infect host cells. Herein, we review the current knowledge of the innate immune signaling pathways triggered by SARS-CoV-2 with a focus on the type I interferon response, as well as the mechanisms by which SARS-CoV-2 impairs those defenses.